Taller de entrenamiento en técnicas asertivas para potenciar las conductas prosociales en las estudiantes del décimo grado paralelo b, de la unidad educativa particular Santa Mariana de Jesús, 2019-2020 - Orellana Sánchez., Jose Enrique (2021)
Prosocial behaviors are an essential part of human activity and maximum representative of the relationships we establish with others, which is why this thesis entitled: Training workshop on assertive techniques to enhance prosocial behaviors in students of the tenth grade parallel B, of the Unidad Educativa Particular Santa Mariana de Jesús, 2019-2020, the objective of this study was to: determine the manifestations of prosocial behavior in students of the tenth grade parallel "B"; thus, it was a quantitative, descriptive, non-experimental, cross-sectional research, based on scientific theoretical methods; the Pro-social Behavior Questionnaire was used with a sample of 29 students. The results show that 59% of the population has low levels of empathy, 52% has low levels of respect, 59% has low levels of sociability and 45% has low levels of leadership, concluding that prosocial behaviors in the investigated population have high percentages in low levels of each evaluation area, and in view of these deficiencies, the proposal is designed through the Workshop for the Assertive Techniques Training to enhance prosocial behaviors.